Human Heat Energy Harvesting Using Thermoelectric Cooler - Wong , Hui Ping (2014)
An extensive research in renewable energy harvesting is increasing due to the limitation of energy resources. The known leading renewable energy harvesting sources is such as hydroelectricity, wind and solar. This research will focus on the human heat energy harvesting which will convert human waste heat to electricity. It focuses on converting the waste heat to electricity from five area of human body such as human palm, top palm, wrist, top wrist and leg. Thermoelectric cooler is used to convert the human body heat to electricity. In this research, a booster circuit is developed to boost the small voltage to higher voltage in order to power up an LED as output indicator. Based on experimental results, the maximum output voltage from Peltier module is obtained from human palm which is 0.1 V. The voltage is able to be boosted up to 2.9 V at the voltage booster output. The output voltage generated at load is 2.47 V and the power output is 24.7 mW. The prototype board built is able to generate human heat as electricity. Human palm is the most suitable location to power-up the LED.